Organic solvents as carrier of thiophanate-methyl into soybean seeds and control of charcoal rot - and M. SRINIVAS PRASAD*, B. SANTHA LAKSHMI*, J.P. GUPTA (Indian Phytopathology, 2002)
The systemic fungicide thiophanate-methyl was carried into soyabean (cv. Bragg) seeds when the seeds were soaked in the fungicide dissolved in ethanol, dichloromethane [methylene chloride] (DCM), trichloromethane (TCM) or acetone. However, benzene and carbon tetrachloride failed to act as carriers. Fungicide penetration increased with increasing fungicide concentration. Percentage emergence of soyabean seeds treated with thiophanate-methyl in different organic solvents was significantly higher thanuntreated seeds. Soaking of soyabean seeds in organic solvents alone improved emergence in comparison with the control. Fungicide in ethanol, DCM, TCM and acetone was superior to the other solvents in controlling charcoal rot disease of soyabean causedby Macrophomina phaseolina.